Pemberdayaan Karyawan Melalui Program Inovasi Digital: Studi Literatur - Deddy Junaedi; Dela Apriliasaidah; Ledi Diana Agustin; Fathimah Nur Aini; Tutik Handayani (HATTA : Jurnal Pendidikan Ekonomi dan Ilmu Ekonomi, 2023)
In the business world, it is difficult to remain innovative and competitive in today's digital era. The aim of this research is to see how digital innovation can encourage employees to increase company efficiency and productivity. This research collects and analyzes various sources about the relationship between employee empowerment and digital innovation. The research results show that digital innovations, such as communication tools and collaboration platforms, increase employee creativity, collaboration and participation. Additionally, technology-based training improves performance and helps employees adapt. To gain a competitive advantage in the market, companies must implement employee empowerment and digital innovation strategies. These results provide important knowledge about human resource management on how to create an empowering and innovative work environment